Preparation method of efficient anti-reflection film for photovoltaic glass and film
By preparing a high-efficiency anti-reflection and anti-reflection film on the surface of photovoltaic glass, the anti-reflection rate in the near-infrared band is controlled to be low and the anti-reflection rate in other bands is high. This solves the photovoltaic problem caused by the increase in transmittance of the existing film in the short-wavelength near-infrared band. The problem of component temperature rise improves the utilization rate and output efficiency of solar energy.
Patent Information
- Application Number
- CN202411349738.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing anti-reflection films have good penetration enhancement effect within the full spectrum range, but the increase in transmittance in the near-infrared short-wavelength band leads to an increase in the temperature of the photovoltaic module, thereby reducing the solar energy output efficiency.
The preparation method of an efficient increase in anti -thin film is used to use a photovoltaic glass. By processing photovoltaic glass, preparing composite solids and adding silicate ethyl acetate, methyl trimal oxygenosiline and other raw materials, forming high -efficiency increased transliteration and anti -coating. The solution is prepared to prepare a thin film on the surface of the photovoltaic glass on the surface of the photovoltaic glass.
In the low -infrared short -band increase rate, the increase in other bands is higher, which improves the utilization of solar energy, reduces the temperature of photovoltaic components, thereby improving the efficiency of solar energy output.
Smart Images

Figure CN119349894A_ABST
Abstract
Description
Technical Field
[0001] This patent relates to the technical field of preparation of anti-reflection and anti-reflection films, and specifically to a method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass. Background Art
[0002] Solar energy is a renewable energy source with the advantages of being clean, safe, sufficient and widespread. Photovoltaic power generation brings significant economic and social benefits and occupies an important position in my country's energy strategy. Improving the utilization rate of sunlight, photoelectric conversion efficiency and reducing manufacturing costs are key issues that need to be addressed in the development of solar cell technology and the photovoltaic industry. Solar cells can be divided into two categories: crystalline silicon cells and thin-film cells. Both use photovoltaic glass as a packaging cover. Therefore, the glass cover is one of the important factors affecting the utilization rate and conversion efficiency of sunlight. Relevant studies have shown that increasing the transmittance of the glass cover by 1% can increase the overall efficiency of the system by 2%. By preparing a high-performance anti-reflection and anti-reflection film on the surface of the photovoltaic glass cover, the reflection of sunlight on the photovoltaic glass can be significantly reduced, the utilization rate of solar energy can be increased, and the photoelectric conversion efficiency can be improved.
[0003] Antireflective coating, also known as AR coating, can effectively reduce the reflection of light at the interface and improve the transmittance by coating it on the surface of optical components. By preparing a nano-thick thin film coating on the surface of the photovoltaic glass cover, the overall transmittance can be effectively improved. However, all antireflective films currently developed and applied have good antireflective effects in the full spectrum (380-1100nm). While the transmittance is improved, the temperature inside the system will increase significantly due to increased heat absorption. Among them, the increase in transmittance in the near-infrared short-wave band (780-1100nm) is the main factor for the temperature increase of photovoltaic modules. However, the transmittance curve of the existing coating shows a smooth decline in the near-infrared short-wave band. The rise in temperature will reduce the conversion efficiency of photovoltaic modules, thereby reducing the efficiency of solar energy output. Therefore, it is an urgent problem to develop a method for preparing an antireflective film that has a less increase in transmittance in the near-infrared band, a greater increase in transmittance in other bands, and a low manufacturing cost and simple construction. Summary of the invention
[0004] In order to overcome the shortcomings of existing anti-reflection and anti-reflection films, the present invention provides a method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass, which can be used to prepare an anti-reflection and anti-reflection film on the surface of photovoltaic cover glass, which has a smaller increase in transmittance in the near-infrared short-wave band and a larger increase in transmittance in other bands.
[0005] The technical problem solved by the present invention is achieved by adopting the following technical solutions:
[0006] First, the present application provides a method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass, comprising the following steps:
[0007] (1) Pretreatment of photovoltaic glass: Use deionized water, dilute hydrochloric acid and anhydrous ethanol to clean, soak and dry the photovoltaic glass substrate in sequence; the pretreatment step can decontaminate and activate the surface of the glass substrate, which is beneficial to enhance the bonding between the anti-reflection film and the substrate.
[0008] (2) Preparation of composite sol: Tetraethyl silicate, anhydrous ethanol, F127 (poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol)), hydrochloric acid, boric acid and deionized water are used as raw materials, and after stirring, mixing and aging, a composite sol is obtained for use.
[0009] (3) Preparation of anti-reflection coating solution: Tetraethyl silicate and methyltriethoxysilane are added to the composite sol prepared in step (2) in sequence, and after stirring, mixing and aging, a high-efficiency anti-reflection coating solution is obtained; the composite sol of step (2) is introduced into a double silicon source together with step (3), and boric acid is introduced at the same time, so that after the reaction, a film with a special pore structure formed by disorderly stacking of SiO2 particles of two different sizes is generated, so as to facilitate the formation of a thin film with a special pore structure in the subsequent steps.
[0010] (4) Preparation of anti-reflection film: The high-efficiency anti-reflection coating solution prepared in step (3) is coated on the glass substrate pretreated in step (1) by an immersion and pulling method. After standing and high-temperature tempering treatment, the high-efficiency anti-reflection film is formed on the photovoltaic glass substrate.
[0011] Furthermore, in the above step (1), the specific steps of pretreatment of photovoltaic glass are: first, rinse the surface of photovoltaic glass with deionized water; then soak the photovoltaic glass in a hydrochloric acid solution with a concentration of 0.3-0.5 mol / L for 10-12 minutes, take it out and continue to rinse it with deionized water; next, use deionized water and anhydrous ethanol to ultrasonically clean the photovoltaic glass for 7-10 minutes in turn; finally, place the cleaned photovoltaic glass in a vacuum drying oven at 80°C for drying.
[0012] Furthermore, in the above step (2), the ratio of the composite sol is: by mass, tetraethyl silicate (C8H 20 O4Si): 23-28, anhydrous ethanol: 54-58, F127: 3.6-7.2 parts, hydrochloric acid: 0.3-0.4, boric acid: 0.9-3, deionized water: 8.7-9.5; the stirring and mixing refers to: carrying out in a magnetic stirrer, the stirring speed is 500-600r / min, and the stirring time is 1-1.5h; the aging refers to: sealing the mixed solution and standing at room temperature for 7d.
[0013] Furthermore, in the above step (2), the mass percentage concentration of tetraethyl silicate used is 99%, the mass fraction of hydrochloric acid is 37%, and the mass percentage concentration of anhydrous ethanol is ≥ 99.7%. The molecular weight of F127 is 15,000.
[0014] Furthermore, in the above step (3), the preparation process of the anti-reflection coating solution is as follows: 90.8 parts by mass of the composite sol are taken, tetraethyl silicate (C8H 20 6.9-11.5 parts of C7H18O4Si) are added to the composite sol, and stirred evenly in a magnetic stirrer at a speed of 500-600r / min for 1-1.5h; after standing and aging at room temperature for 2d under sealed conditions, 2.3-2.8 parts of methyltriethoxysilane (C7H18O3Si) are added to the mixed solution, and stirred evenly in a magnetic stirrer at a speed of 500-600r / min for 1-1.5h; and then standing and aging at room temperature for 3d under sealed conditions to obtain a high-efficiency anti-reflection coating solution.
[0015] Furthermore, in the above step (4), the immersion pulling is carried out in an immersion pulling machine, the immersion speed is 3000-4000 μm / s, the immersion time is 10-12s, the pulling speed is 500-600 μm / s, and the environmental conditions are: temperature 20-30°C, relative humidity 40% to 60%.
[0016] Furthermore, in the above step (4), the specific process of the standing and high-temperature tempering treatment is: standing in the atmosphere for 20-30 minutes; tempering is carried out in a muffle furnace at a tempering temperature of 730-740°C for 90-120 seconds to obtain the above-mentioned high-efficiency anti-reflection and anti-transmission film.
[0017] Secondly, the present application provides a high-efficiency anti-reflection and anti-reflection film obtained by the above method.
[0018] In the technical solution of the present application, boric acid is added during the preparation of the composite sol in step (2), and other silicon sources are added during the preparation of the anti-reflection coating solution in step (3), so that the cross-linked network structure in the sol in the anti-reflection coating solution becomes denser and the tendency of particle agglomeration increases. Large particles generated by partial particle agglomeration in the system coexist with small particles that have not agglomerated, so that the prepared film has a lower transmittance gain for light of near-infrared wavelength (780-1100nm).
[0019] The advantages and beneficial effects of the present invention are:
[0020] (1) The anti-reflection film prepared on the surface of photovoltaic glass by this method has a lower transmittance near the near-infrared short-wave band and a higher transmittance in other bands, thereby improving the utilization rate of solar energy.
[0021] (2) The raw materials used in the present invention are easy to obtain, inexpensive, safe and non-toxic.
[0022] (3) The preparation steps of the present invention are simple, convenient and easy to implement, and have no special requirements for production equipment, which is conducive to industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the high-efficiency anti-reflection and anti-transmission film for photovoltaic glass prepared in Example 1.
[0024] Figure 2 This is the transmittance curve of the high-efficiency anti-reflection and anti-reflection film for photovoltaic glass prepared in Example 1. DETAILED DESCRIPTION
[0025] The following examples use tetraethyl silicate with a mass percentage concentration of 99% (actual mass in the examples, the same below), anhydrous ethanol with a mass percentage concentration of ≥99.7%, F127 molecular weight of 15,000, methyltriethoxysilane with a mass percentage concentration of 98%, and boric acid solid powder with a mass percentage concentration of 99%, all of which were purchased from Shanghai Aladdin Reagent Co., Ltd. The mass percentage concentration of hydrochloric acid is 37%, purchased from Nanjing Chemical Reagent Co., Ltd. K9 photovoltaic glass was purchased from Changchun Aopu Optoelectronics Technology Co., Ltd.
[0026] The stirring device used in the following examples is a heat-collecting magnetic stirrer (DF-101S) produced by Shanghai Lichen Bangxi Instrument Technology Co., Ltd., the immersion coating machine (SC-DP-1) is produced by Beijing Saidekaisi Electronics Co., Ltd., and the muffle furnace (SX-6-17) is produced by Shanghai Caixing High Temperature Component Electric Furnace Factory.
[0027] The transmittance of the anti-reflection film prepared in the following embodiments is tested using the BTG-8 photovoltaic glass spectral transmittance tester produced by Qinhuangdao Xianhe Technology Co., Ltd. in accordance with GB / T2410-2024, and the test wavelength range is 380-1100nm. The hardness of the anti-reflection film is tested using the QHQ-A portable pencil scratch tester produced by Aripus Corporation in accordance with GB / T6739-2022.
[0028] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to these.
[0029] Example 1
[0030] 1. Pretreatment of photovoltaic glass: Select K9 photovoltaic glass as the substrate, first rinse the surface of the photovoltaic glass with deionized water; then soak the photovoltaic glass in a diluted hydrochloric acid solution with a concentration of 0.3 mol / L for 10 minutes, take it out and continue to rinse it with deionized water; then use deionized water and anhydrous ethanol to ultrasonically clean the substrate for 7 minutes; finally, put the cleaned photovoltaic glass into a vacuum drying oven at 80°C and dry it for 15 minutes.
[0031] 2. Preparation of composite sol: Tetraethyl silicate, anhydrous ethanol, F127, hydrochloric acid, boric acid, and deionized water are used as raw materials. The mass fractions of the composite sol are as follows: tetraethyl silicate: 23, anhydrous ethanol: 54, F127: 3.6 parts, hydrochloric acid: 0.3, boric acid: 0.9, and deionized water: 8.7. The above mixture is stirred in a magnetic stirrer at a stirring speed of 500r / min for 1h; then the mixed solution is sealed and allowed to stand at room temperature for 7d to obtain a composite sol.
[0032] 3. Preparation of anti-reflection coating solution: Take 90.8 parts of the composite sol prepared in step 2, add 6.9 parts of tetraethyl silicate to the composite sol, stir in a magnetic stirrer, the stirring speed is 500r / min, and the stirring time is 1h; seal the mixed solution, let it stand at room temperature, and age for 2d; then add 2.3 parts of methyltriethoxysilane to the above mixed solution, stir in a magnetic stirrer, the stirring speed is 500r / min, and the stirring time is 1h; then seal the mixed solution, let it stand at room temperature, and age for 3d, so as to obtain a high-efficiency anti-reflection coating solution for photovoltaic glass.
[0033] 4. Preparation of anti-reflection film: The environmental conditions for preparing the coating are as follows: at a temperature of 20°C and a relative humidity of 40%, firstly, the pretreated photovoltaic glass and the high-efficiency anti-reflection coating solution prepared in step (3) are placed in an immersion and pulling machine at a dipping speed of 3000 μm / s and a dipping time of 10 s; then, the film is pulled at a pulling speed of 500 μm / s; then, it is allowed to stand in the air for 20 minutes; and then, it is placed in a muffle furnace preheated to 730°C and tempered for 120 seconds to obtain a high-efficiency anti-reflection film for photovoltaic glass.
[0034] The SEM image of the high-efficiency anti-reflection and anti-reflection film for photovoltaic glass prepared in this embodiment is as follows: Figure 1As shown, it can be seen that the prepared film (coating) is mainly composed of granular silicon dioxide, and some large particles formed by the aggregation of small silicon dioxide particles can be observed. After testing, the high-efficiency anti-reflection film prepared in this embodiment has a transmittance of 94.34% in the full wavelength range of 380-1100nm, of which the transmittance in the visible light range is 95.46%, and the transmittance in the near-infrared wavelength range (780-1100nm) is 93.64%, and the hardness of the film is 3H.
[0035] Figure 2 This is the transmittance curve of the high-efficiency anti-reflection and anti-transmittance film for photovoltaic glass prepared in this embodiment. It can be seen that the film (coating) prepared in this embodiment has the characteristics of high transmittance gain in the visible light band and low transmittance gain in the near-infrared short-wave band (obvious pits appear in the curve).
[0036] Example 2
[0037] 1. Pretreatment of photovoltaic glass: Select K9 photovoltaic glass as the substrate. First, rinse the surface of the photovoltaic glass with deionized water; then soak the photovoltaic glass in a diluted hydrochloric acid solution with a concentration of 0.4 mol / L for 11 minutes, and then continue to rinse with deionized water after taking it out; then use deionized water and anhydrous ethanol to ultrasonically clean the substrate for 8 minutes in turn; finally, put the cleaned photovoltaic glass into a vacuum drying oven at 80°C for drying.
[0038] 2. Preparation of composite sol: Tetraethyl silicate, anhydrous ethanol, F127, hydrochloric acid, boric acid, and deionized water are used as raw materials. The mass fractions of the composite sol are as follows: tetraethyl silicate: 25, anhydrous ethanol: 56, F127: 5.0 parts, hydrochloric acid: 0.4, boric acid: 2.0, and deionized water: 9.2. The above mixture is stirred in a magnetic stirrer at a stirring speed of 550r / min for 1.5h; then the mixture is sealed and allowed to stand at room temperature for 7d.
[0039] 3. Preparation of anti-reflection and anti-reflection coating solution: Take 90.8 parts of composite sol, add 8.5 parts of tetraethyl silicate to the composite sol, stir in a magnetic stirrer at a speed of 550 r / min for 1.5 hours; seal the mixed solution, let it stand at room temperature, and age for 2 days; then add 2.5 parts of methyltriethoxysilane to the above mixed solution, stir in a magnetic stirrer at a speed of 550 r / min for 1.5 hours; seal the mixed solution, let it stand at room temperature, and age for 3 days to obtain a high-efficiency anti-reflection and anti-reflection coating solution for photovoltaic glass.
[0040] 4. Preparation of anti-reflection film: The environmental conditions for preparing the coating are as follows: at a temperature of 25°C and a relative humidity of 50%, firstly, the pretreated photovoltaic glass and the high-efficiency anti-reflection coating solution prepared in step (3) are placed in an immersion and pulling machine at a dipping speed of 3500 μm / s and a dipping time of 12 s; then, the film is pulled at a pulling speed of 550 μm / s; then, it is allowed to stand in the air for 25 minutes; and then, it is placed in a muffle furnace at 740°C and tempered for 90 seconds to obtain a high-efficiency anti-reflection film for photovoltaic glass.
[0041] After testing, the high-efficiency anti-reflection and anti-reflection film prepared in this embodiment has a transmittance of 94.77% in the wavelength range of 380-1100nm, a transmittance of 95.61% in the visible light range, and a transmittance of 93.58% in the near-infrared wavelength range (780-1100nm). The hardness of the film is 3H.
[0042] Example 3
[0043] 1. Pretreatment of photovoltaic glass: Select K9 photovoltaic glass as the substrate, first rinse the surface of the photovoltaic glass with deionized water; then soak the photovoltaic glass in a diluted hydrochloric acid solution with a concentration of 0.5 mol / L for 12 minutes, take it out and continue to rinse it with deionized water; then use deionized water and anhydrous ethanol to ultrasonically clean the substrate for 10 minutes in turn; finally, put the cleaned photovoltaic glass into a vacuum drying oven at 80°C for drying.
[0044] 2. Preparation of composite sol: Tetraethyl silicate, anhydrous ethanol, F127, hydrochloric acid, boric acid, and deionized water are used as raw materials. The mass fractions of the composite sol are as follows: tetraethyl silicate: 28, anhydrous ethanol: 58, F127: 7.2 parts, hydrochloric acid: 0.35, boric acid: 3.0, and deionized water: 9.5. The above mixture is stirred in a magnetic stirrer at a stirring speed of 600r / min for 1.2h; then the mixture is sealed and allowed to stand at room temperature for 7d.
[0045] 3. Preparation of anti-reflection coating solution: Take 90.8 parts of composite sol, add 11.5 parts of tetraethyl silicate to the composite sol, stir in a magnetic stirrer, the stirring speed is 600r / min, and the stirring time is 1.3h; the mixed solution is sealed, allowed to stand at room temperature, and aged for 2d; then 2.8 parts of methyltriethoxysilane are added to the above mixed solution, stirred in a magnetic stirrer, the stirring speed is 600r / min, and the stirring time is 1.3h; the mixed solution is sealed, allowed to stand at room temperature, and aged for 3d, to obtain a high-efficiency anti-reflection coating solution for photovoltaic glass.
[0046] 4. Preparation of anti-reflection film: The environmental conditions for preparing the coating are as follows: at a temperature of 30°C and a relative humidity of 60%, firstly, the pretreated photovoltaic glass and the high-efficiency anti-reflection coating solution prepared in step (3) are placed in an immersion and pulling machine at a dipping speed of 4000 μm / s and a dipping time of 11 s; then, the film is pulled at a pulling speed of 600 μm / s; then, it is allowed to stand in the air for 30 minutes; and then, it is placed in a muffle furnace at 735°C for tempering for 100 seconds to obtain a high-efficiency anti-reflection film for photovoltaic glass.
[0047] After testing, the high-efficiency anti-reflection and anti-reflection film prepared in this embodiment has a transmittance of 94.18% in the wavelength range of 380-1100nm, a transmittance of 95.23% in the visible light range, and a transmittance of 93.61% in the near-infrared wavelength range (780-1100nm). The hardness of the film is 3H.
[0048] The above embodiments are only used to illustrate the contents of the present invention rather than to limit the present invention. Therefore, any changes within the meaning and scope equivalent to the claims of the present invention should be considered to be included in the scope of the claims.
[0049] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass, characterized in that: The specific steps are as follows: 1) Clean and dry the photovoltaic glass as a glass substrate for future use; 2) Tetraethyl silicate, anhydrous ethanol, F127, hydrochloric acid, boric acid and deionized water are mixed and aged to obtain a composite sol for later use; In the composite sol, by weight, tetraethyl silicate: 23-28 parts, anhydrous ethanol: 54-58 parts, F127: 3.6-7.2 parts, hydrochloric acid: 0.3-0.4 parts, boric acid: 0.9-3 parts, deionized water: 8.7-9.5 parts; 3) adding tetraethyl silicate and methyltriethoxysilane to the composite sol, and obtaining a coating solution after aging; 4) The coating solution is applied to the surface of the glass substrate obtained in step 1), and after standing and high-temperature tempering treatment, the high-efficiency anti-reflection and anti-reflection film is formed on the surface of the photovoltaic glass substrate.
2. The method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass according to claim 1, characterized in that: Step 1) The cleaning refers to: first rinsing the photovoltaic glass with deionized water, then soaking it in a hydrochloric acid solution, then rinsing it again with deionized water, and finally ultrasonically cleaning the photovoltaic glass with deionized water and anhydrous ethanol in sequence.
3. The method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass according to claim 1, characterized in that: Step 2) The mixing refers to stirring and mixing for 1-1.5 hours; the aging refers to standing and aging at room temperature for 7 days under sealed conditions.
4. The method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass according to claim 1, characterized in that: Step 3) Adding tetraethyl silicate and methyltriethoxysilane to the composite sol means, by weight, adding 6.9-11.5 parts of tetraethyl silicate to 90.8 parts of the composite sol, stirring for 1-1.5 hours; then standing and aging at room temperature for 2 days under sealed conditions to obtain a mixed solution; then adding 2.3-2.8 parts of methyltriethoxysilane to the mixed solution, stirring for 1-1.5 hours; then standing and aging at room temperature for 3 days under sealed conditions to obtain a high-efficiency anti-reflection coating solution for photovoltaic glass.
5. The method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass according to claim 1, characterized in that: Step 4) The coating refers to coating the high-efficiency anti-reflection coating solution on the surface of the glass substrate by immersion and pulling method, with an immersion speed of 3000-4000 μm / s, an immersion time of 10-12s, and a pulling speed of 500-600 μm / s.
6. The method for preparing a high-efficiency anti-reflection and anti-reflection film for photovoltaic glass according to claim 1, characterized in that: Step 4) The static and high temperature tempering treatment refers to, after static standing for 20-30 minutes, tempering at 730-740° C. for 90-120 seconds.
7. A high-efficiency anti-reflection and anti-transmission film for photovoltaic glass prepared by any method of claims 1-6.
Citation Information
Patent Citations
Sol liquid of solar photovoltaic glass double-faced single-layer antireflection film, preparation method and film coating method
CN103984046A
Preparation method of film-plating liquid for antireflection film of high anti-weathering type photovoltaic glass
CN105130205A
Netlike SiO2 coated sol, and preparation method and application thereof
CN108545753A
Preparation method of modified porous silicon dioxide moisture-proof anti-reflection coating
CN109592908A
Method for rapidly preparing hollow silicon dioxide and coating capable of refracting specific wavelength
CN111320179A
Cited By
Low-reflection anti-dazzle high-transmission conductive glass and preparation method thereof
CN122145046A